Living trusts - Moy, Doug H. (Hoboken, N.J. : J. Wiley & Sons, 2003)
(NtOW^ HURAANGUJs
Continuing need for estate planning -- Framework of a revocable living trust -- Trustee's powers, duties, and responsibilities -- Property management and other benefits -- Disadvantages, reservations, and limitations of a revocable living trust -- Lifetime operation of a revocable living trust -- Federal income tax -- Federal and state transfer taxes -- Overview of the funding process -- Real property interests -- Publicly-traded securities and U.S. government obligations -- Closely-held business interests -- Acounts inbanks, saving associations, and credit unions -- Tangible and intangible personal property -- Qualified and nonqualified retirement plans -- Life insurance and annuities -- Power of attorney and pour-over will .
Includes bibliographical references (p. 391-397) and index.
Keywords: Living trusts -- United States